Downstream extraction process development for recovery of organic acids from a fermentation broth. (November 2016) - Bekatorou, Argyro; Dima, Agapi; Tsafrakidou, Panagiotia; Boura, Konstantina; Lappa, Katerina; Kandylis, Panagiotis; Pissaridi, Katerina; Kanellaki, Maria; Koutinas, Athanasios A.
Highlights: A downstream extraction process for organic acids recovery is proposed. Factors like pH, solvent/OAs solution ratios affect the extraction. Alcohols presented the best extraction performance. 3-Methyl-1-butanol led to the highest recovery. Abstract: The present study focused on organic acids (OAs) recovery from an acidogenic fermentation broth, which is the main problem regarding the use of OAs for production of ester-based new generation biofuels or other applications. Specifically, 10 solvents were evaluated for OAs recovery from aqueous media and fermentation broths. The effects of pH, solvent/OAs solution ratios and application of successive extractions were studied. The 1:1 solvent/OAs ratio showed the best recovery rates in most cases. Butyric and isobutyric acids showed the highest recovery rates (80–90%), while lactic, succinic, and acetic acids were poorly recovered (up to 45%). The OAs recovery was significantly improved by successive 10-min extractions. Alcohols presented the best extraction performance. The process using repeated extractions with 3-methyl-1-butanol led to the highest OAs recovery. However, 1-butanol can be considered as the most cost-effective option taking into account its price and availability.